A new compact and low-cost respirator concept for one way usage. Issue 27 (2018) - Jürß, H.; Degner, M.; Ewald, H.
Abstract: This paper describes the concept, the design and the construction of an innovative, small-sized and low-cost lung ventilator. The essential part of the respirator is the full face mask, which includes a ventilation blower and integrated sensors. Due to this structure, there is no need for respiration tubes or other external devices. The low-cost as well as the small-sized and compact construction make the respirator suitable for stockpiling and easy transport - well suited for the usage in case of a natural disaster or a pandemic with a large number of patients. Integrated sensors for airflow and airway pressure enable safe operation and the monitoring of relevant respiration data. The designed and built prototype was tested and verified in a pneumatical testing environment. By using an approved mathematical lung model, disturbances like airway occlusion and leakages can be detected by the system and partly compensated. The measurements show the functionality of the developed respirator mask and verify the concept of a full face mask with a sensor controlled, integrated ventilation blower as a suitable respirator for emergency or resource poor environments.